Oil price changes and trade openness in Nigeria: linear and nonlinear approach - Bala, Umar; Lee, Chin; Maijama’a, Rabiu (International Journal of Economics, Commerce and Management (IJECM), 2019)
This empirical research examines the relations between trade openness and oil price changes in Nigeria between the period of 1982 to 2014 using linear and nonlinear autoregressive distributed lags models. The ARDL bounds test shows the existence of cointegration, we further estimate the model using NARDL specification and discovered the existence of a long-run relationship among the variable that means they are cointegrated in nonlinearity. In the long run, the study found that when the oil price rises trad e openness affected significantly. But, when oil price dropped is not significant. The policymakers should consider the different policy between increases and decreases in oil prices when oil price increases have to monitor the degree of open-up than when oil prices dropped. Ordinarily, the foreign trade in oil producing countries is protected by trade restrictions during low oil price The policy has to take major on the exchange rate policy since depreciation can make the trade more open-up.